Fast Food Consumption Pattern and Its Association with Overweight Among High School Boys in Mangalore City of Southern India - Joseph, Nitin (J Clin Diagn Res, 2015)
CONTEXT: Fast foods are quite popular among children owing to taste, appearance and hype created by mass media. However, the increased incidence of lifestyle disorders seen now-a-days at an early age could be attributed to fast foods. AIM: This study was done to assess the awareness of health hazards, consumption pattern of fast foods and to find out its association with overweight among high school students. SETTINGS AND DESIGN: This cross-sectional study was done among boys of 3 private schools in Mangalore city in March 2012. MATERIALS AND METHODS: Data was collected using a semi-structured self-administered questionnaire. STATISTICAL ANALYSIS: Chi-square test, one-way ANOVA and binary logistic regression analysis was used for analysis. P-value ≤ 0.05 was considered as statistically significant association. RESULTS: Mean age of boys was 13.5±0.9 years. Out of 300 participants, 41(13.7%) were overweight and 8 (2.7%) were obese. 292(97.3%) were fast food users of which 42(14.4%) consumed it every day. Majority of participants were introduced to fast foods through television commercials 193(64.3%). 73(57%) developed this habit as they were bored with home food. Awareness of harmful effects of fast food consumption was known to 186(62%) students and this was found to be associated with the perceived need to control its usage (p<0.001). Parental consumption of fast foods was found to influence fast food consumption among children (p=0.024). As many as 68(22.7%) and 206(68.7%) children were not eating vegetables and fruits respectively every day. Increased frequency of fast food consumption in a week was found to be associated with overweight or obesity among children after adjusting the effects of confounders (p=0.003). CONCLUSION: Awareness on health hazards of fast foods needs to be taught at schools so as to minimize its consumption. Parents have to set an example themselves by not eating fast foods and improving home food to support discouragement of fast foods. This would minimize life style disorders among children to a greater extent.